Humour as an act of deracination and native resistance through alterity, subaltern and negritude in selected plays by Francis Davis Imbuga - A. Majeed, Abdulhameed (2021)
This research studied the cultural intersection between modernity and tradition through humour deracination in Imbuga’s Betrayal in the City (1976), The Green Cross of Kafira (1984), Aminata (1988), and The Burning of Rags (1989). It focused on the native Kenyan ethnicity as an exemplification of inherited tradition that attempts to oppose the British cultural modernity for the sake of empowering the native identity. Therefore, the research untraveled verbal humour and farcical situations of the selected plays as a way of rejecting the colonial culture. Consequently, the study of humour revealed it as an act of deracination and native resistance. The interpretation of such resistance was reinforced by highlighting the society of the native Kenyan people as negritude. Such negritude society is treated as subaltern ethnicity, which indicates their inferior state. On the other hand, the British colonial ethnicity was tackled as oppressive alterity, or othering, that tries to impose its colonial culture upon the natives. The research achieved three objectives, namely (1) To explore the native Kenyan cultural identity as a manifestation of tradition that contradicts with British modernity culture in the selected plays, (2) To investigate the Kenyan society as being negritude which is perceived as subaltern ethnicity attempting to resist the colonial persecutory alterity by applying Taussig’s concept of alterity and Spivak’s concept of subaltern, and (3) To examine Imbuga’s depiction of native Kenyan cultural tradition that resists the colonial modernity through humour deracination to empower their inherited identity by applying Fanon’s concept of deracination. The achievement of these objectives was elaborated in terms of post-colonialism as a conceptual framework, and the selected concepts were limited to Michael Taussig’s concept of alterity, Gayatri Chakravorty Spivak’s concept of subaltern, and Frantz Fanon’s concept of deracination. The aim of the study was to demonstrate how verbal humour and situational farce could be employed to restrict the cultural spread of colonial culture in Kenya. The findings of the study are underpinned in three interrelated tenets. First, the Kenyan cultural traditions incarnate the authentic social aboriginality before the advent of colonialism. Second, humour is a way of deracinating the influence of the British hegemony upon the traditional Kenyan ethnicity. Third, deracination is an empowerment of the native identity. Thus, the significance of the research lies in its exploration of the way by which the Kenyan natives could preserve their ancestors’ identity and traditions, which reflects the novelty of the research’s dual study of humour and deracination in the light of post-colonialism.